Shear resistance and composition of polyethylene protuberances from hip-simulating pin-on-disc wear tests. (September 2020) - Heuberger, Roman; Bortel, Emely Lea; Sague, Jorge; Escuder, Pablo; Nohava, Jiri
Abstract: Protuberances on the surface of ultra-high-molecular-weight polyethylene (UHMWPE) pins were chemically and mechanically investigated in order to better understand the tribology of UHMWPE vs. CoCrMo, which is a typical material pairing for joint replacements. Pin-on-disc wear tests were performed using pins made of UHMWPE articulating against discs made of a CoCrMo alloy. Wear tests were performed using two different test fluids: a standard test liquid used for hip-simulator tests and a synthetic synovial fluid containing hyaluronic acid, albumin, immunoglobulin G, the phospholipid lecithin and additionally sodium azide to fight bacterial growth. After the wear tests, the pin surfaces exhibited scratches as well as protuberances with a pitting-like appearance. These protuberances, i.e. elevations protruding from the articulating surface, were 6 ± 3 μm high on the pins lubricated with the standard test liquid and 20 ± 5 μm high under the lubrication with the synthetic synovial fluid. Investigating the protuberances using Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) showed that these were composed mainly of UHMWPE, together with amine groups from proteins. To our knowledge, the mechanical properties and namely shear resistance of these protuberances were investigated the first time. The hardness and the elastic modulus of the protuberances were similar to the bulk material, as revealed by nanoindentation. The shear resistance of the protuberances as measured by a nanoscratch test method was comparable or even higher than that of the bulk material. Highlights: Protuberances investigated to better understand the tribology of UHMWPE vs. CoCrMo. Protuberances were composed of UHMWPE, together with amine groups from proteins. Shear resistance of protuberances was investigated using a nanoscratch test method. High shear resistance of the protuberances, similar or higher than bulk material.